2007
DOI: 10.1007/s12028-007-0008-x
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of S100B in predicting severity of central nervous system injury

Abstract: S100B is a protein biomarker that reflects CNS injury. It can be measured in the CSF or serum with readily available immunoassay kits. The excellent sensitivity of S100B has enabled it to confirm the existence of subtle brain injury in patients with mild head trauma, strokes, and after successful resuscitation from cardiopulmonary arrest. The extent of S100B elevation has been found to be useful in predicting clinical outcome after brain injury. Elevations of S100B above certain threshold levels might be able … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(133 citation statements)
references
References 148 publications
(216 reference statements)
3
119
0
4
Order By: Relevance
“…In Patienten, die eine TTMBehandlung erhielten, variierte die NSESchwellenkonzentration für 0 % FPR zwischen 49,6 und 151,4 µg/l bei 24 h [313,[322][323][324][325][326] [330][331][332] [323,324,334]. In einer Sekundärana -lyse der TTM-Studie wurden die NSESerumkonzentrationen nach 24, 48 und 72 h bei 686 Patienten gemessen.…”
Section: Neuronenspezifische Enolase (Nse)unclassified
“…In Patienten, die eine TTMBehandlung erhielten, variierte die NSESchwellenkonzentration für 0 % FPR zwischen 49,6 und 151,4 µg/l bei 24 h [313,[322][323][324][325][326] [330][331][332] [323,324,334]. In einer Sekundärana -lyse der TTM-Studie wurden die NSESerumkonzentrationen nach 24, 48 und 72 h bei 686 Patienten gemessen.…”
Section: Neuronenspezifische Enolase (Nse)unclassified
“…S100B is a glial-derived protein that is released by astrocytes in proportion to the degree of brain injury [26]. One study found a 24-h S100B value >1.03 ug/l provided a sensitivity of 94% and a specificity of 83% for the development of malignant edema [27].…”
Section: Malignant Cerebral Edemamentioning
confidence: 99%
“…Existing clinical prognostic tools, based on age, pupil reactivity, and initial GCS [55] do not provide the level of detail that many families seek in their decision-making [26]. Several neuroimaging and blood proteins are used as prognostic biomarkers.…”
Section: Biomarkers For Prognosismentioning
confidence: 99%
See 1 more Smart Citation
“…S100B protein in the serum of patients with traumatic brain injury (TBI) will rise rapidly within 6 hours after injury. Studies[9,10] have proved that the higher level of S100B protein in serum, the more risks the patients with TBI. It is also reported that S100B protein could predict the prognosis of patients with TBI.…”
Section: Introductionmentioning
confidence: 99%